Effect of privatizing Japanese expressway companies on maintenance and management efficiency - Tsubasa Kaino; Kazuyoshi Hidaka (Transport Economics and Management)
In 2005, Japan privatized its four public highway corporations, resulting in the establishment of three NEXCO companies. Although these entities remain fully government-owned, future stock exchange listing is envisioned. To inform discussions on this transition, it is essential to analyze the effects of privatization on management efficiency and identify factors influencing efficiency changes. While a certain degree of progress has been observed in achieving the three objectives articulated by the Japanese government at the time of privatization—namely, the steady repayment of interest-bearing debt, the early and inexpensive construction of expressways, and the provision of various services—these initial goals did not encompass maintenance and operation, which have become increasingly important over time. As a result, the impact of privatization on these aspects remains insufficiently examined. This study therefore focuses on existing expressway segments and investigates changes in maintenance and operational efficiency before and after privatization. Using data envelopment analysis (DEA), we evaluate efficiency based on indicators such as management costs and toll revenue, comparing performance in the pre-privatization period, immediately after privatization, and 14 years later. The results indicate that network-wide efficiency showed little change immediately after privatization. However, route-level analysis reveals a decline in efficiency over time. These findings suggest that privatization, even in the form of a joint stock company, may have limited capacity to enhance long-term management efficiency in expressway operations.